2014
DOI: 10.1371/journal.pone.0087030
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of α-Galactosylceramide Analogs in Activated Microglia: Involvement of the p38 MAPK Signaling Pathway

Abstract: Microglial activation plays a pivotal role in the development and progression of neurodegenerative diseases. Thus, anti-inflammatory agents that control microglial activation can serve as potential therapeutic agents for neurodegenerative diseases. Here, we designed and synthesized α-galactosylceramide (α-GalCer) analogs to exert anti-inflammatory effects in activated microglia. We performed biological evaluations of 25 α-GalCer analogs and observed an interesting preliminary structure-activity relationship in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 43 publications
2
20
0
2
Order By: Relevance
“…HSR1101 exerted significant inhibition of the phosphorylation of all three types of MAPKs (Figure 7). In accordance with these findings and previous reports [20,[28][29][30], U0126, SP600125, and SB203580, the specific inhibitors of MEK1/2, JNK, and p38 MAPK, respectively, suppressed the LPS-induced production of IL-6, TNF-α, and NO (data not shown). Moreover, LPS-induced cell migration was also reduced by these specific MAPK inhibitors (Figure 8).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…HSR1101 exerted significant inhibition of the phosphorylation of all three types of MAPKs (Figure 7). In accordance with these findings and previous reports [20,[28][29][30], U0126, SP600125, and SB203580, the specific inhibitors of MEK1/2, JNK, and p38 MAPK, respectively, suppressed the LPS-induced production of IL-6, TNF-α, and NO (data not shown). Moreover, LPS-induced cell migration was also reduced by these specific MAPK inhibitors (Figure 8).…”
Section: Discussionsupporting
confidence: 92%
“…To elucidate the involvement of MAPKs in the inhibition of pro-inflammatory mediators by HSR1101, we investigated the effects of MAPK inhibitors on the production of pro-inflammatory mediators in LPS-treated BV2 cells. In consistence with the findings reported previously [20,[28][29][30], we also observed in our study that U0126, SP600125 and SB203580, the specific inhibitors of MEK1/2 (a type of MAPK/ERK kinase), JNK and p38 MAPK, respectively, noticeably inhibited LPS-promoted production of IL-6, TNF-α, and NO (data not shown). Furthermore, we found that these MAPK inhibitors significantly attenuated iNOS and COX-2 expression and inhibited nuclear translocation of NF-κB and phosphorylation of IκBα in the LPS-treated BV2 cells (data not shown).…”
Section: Effects Of Mapk Inhibitors On Lps-induced Pro-inflammatory Msupporting
confidence: 93%
See 1 more Smart Citation
“…Jeonget al [58] showed that the anti-inflammatory effect of α-galactosylceramide was mediated by the inhibition of p38 MAPK activation in activated BV2 cells. Kim et al [25] showed that floridoside inhibited p38 and ERK 1/2 phosphorylation but not JNK in LPS-stimulated BV2 cells, while Dong et al [59] showed that oxymatrine significantly inhibited all of the MAPKs, including ERK, p38, and JNK in LPS-induced BV2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mitogen‐activated protein kinases (MAPKs), as another major inflammatory signal, are also involved in regulating the expression of several inflammatory genes. Both in vitro and in vivo studies have shown that activation of MAPKs (ERK, JNK, and p38) is necessary for a number of the inflammatory responses to LPS [Lee et al, ; Jeong et al, ; Zhao et al, ]. For example, p38 and JNK MAPKs activities are strongly enhanced in multiple cell types including glial cells, endothelial cells, and as well as mononuclear macrophages by LPS or inflammatory cytokines through increasing their phosphorylation levels, and further accelerate inflammatory responses; moreover, TNF‐α mRNA transport from the nucleus to the cytoplasm could be blocked by ERK inhibitor [Raingeaud et al, ; Dong and Davis, ; Zhi et al, ].…”
mentioning
confidence: 99%